Azo-polymers photofluidisation – a transient state of matter emulated by molecular motors. Issue 32 (14th March 2016) - Hurduc, N.; Donose, B. C.; Rocha, L.; Ibanescu, C.; Scutaru, D.
Abstract : In the present paper we propose a new phenomenological model of inscription based on a particular state of matter induced by continuous laser irradiation. Abstract : The generation of nanostructured azo-polymer films upon interaction with light of a certain wavelength was reported for the first time more than two decades ago. Despite continuous efforts the mechanism governing structuration remains under debate. In the present paper we propose a new phenomenological model of inscription based on a particular state of matter induced by continuous laser irradiation. The continuous trans – cis – trans motion of azo-segments, resembling molecular motors, induces polymer chain displacement (flowing) even when the irradiated polymer has a very high viscosity. Film surface deformation is the result of two simultaneous processes, one or the other being dominant, as a function of the operational conditions and the azo-polymer chemical structure; the first process, is irreversible and based on the azobenzene molecular motor action leading to polymeric chain displacement (flow) and the second one, is reversible and an elastic deformation induced by the Weigert effect.